Interactive video's urgency on guided inquiry laboratory to improve integrated science process skills - Ince Raudhiah Zahra; Didi Teguh Chandra; Dadi Rusdiana (Jurnal Penelitian Ilmu Pendidikan, 2023)
This study aimed to describe the analysis phase results on the ADDIE product development method, which forms the basis for the need for interactive videos in guided inquiry laboratory learning to improve integrated science process skills. The analytical procedures used were identifying gaps in the performance of students' integrated science process skills, identifying the cause, collecting infrastructure information, and determining appropriate products. Data was collected through tests and questionnaires from 42 students and 7 middle school science teachers in West Java. The results show that students' integrated science process skills are low. The cause is the rare provision of learning that facilitates students to design experiments. Students need more intensive guidance, but teachers have limitations in facilitating all the difficulties students face when designing and conducting experiments. Based on the results of an analysis of student characteristics, teacher difficulties, and availability of infrastructure, the interactive video in guided inquiry laboratory learning is suitable for addressing issues of readiness, time management, and difficulties in guiding students so it is hoped that integrated science process skills can improve. Peningkatan keterampilan proses sains terintegrasi menggunakan video interaktif pada inkuiri laboratorium terbimbingPenelitian ini bertujuan untuk mendeskripsikan hasil fase analisis pada metode pengembangan produk ADDIE yang menjadi dasar diperlukannya video interaktif pada pembelajaran laboratorium inkuiri terbimbing untuk meningkatkan keterampilan proses sains terintegrasi. Prosedur analisis yang digunakan adalah mengidentifikasi kesenjangan keterampilan proses sains terintegrasi peserta didik, mengidentifikasi penyebab kesenjangan, mengumpulkan informasi infrastruktur, dan menentukan produk yang sesuai. Pengumpulan data dilakukan melalui tes dan angket dari 42 peserta didik dan 7 guru IPA SMP di Jawa Barat. Hasil penelitian menunjukkan bahwa keterampilan proses sains terintegrasi peserta didik tergolong rendah. Penyebabnya adalah kurang optimalnya pemberian pembelajaran yang memfasilitasi peserta didik untuk merancang eksperimen. Peserta didik membutuhkan bimbingan yang lebih intensif, namun guru memiliki keterbatasan dalam memfasilitasi semua kesulitan yang dihadapi peserta didik saat merancang dan melakukan percobaan. Berdasarkan hasil analisis karakteristik peserta didik, kesulitan guru, dan ketersediaan sarana prasarana, video interaktif dalam pembelajaran laboratorium inkuiri terbimbing dipilih karena sesuai untuk mengatasi masalah kesiapan, manajemen waktu, dan kesulitan dalam membimbing peserta didik sehingga diharapkan keterampilan proses sains terintegrasi dapat meningkat.